Status of EXO-200 - Perimeter Institute (Perimeter Institute, 2008)
Searches for neutrinoless double beta decays could determine if neutrinos are Majorana particles and could measure their absolute mass scale. The initial stage of the Enriched Xenon Observatory project, EXO-200, will look for two-neutrino and neutrinoless double-beta decays of Xe-136 in a liquid-xenon time-projection chamber. By combining the ionization signal with detection of the scintillation light collected in Large Area Avalanche Photodiodes (LAAPDs), an energy resolution of about 1.4% at the decay energy can be achieved. All construction materials have been systematically selected to minimize naturally-occurring radioactive impurities. An active muon veto is presently under construction. Using these background reduction techniques and the available 200 kg of isotopically enriched xenon (80% in Xe-136), EXO-200 will be soon able to test present constraints on the effective Majorana-neutrino mass. It will also serve to demonstrate the potential performance of a larger-scale EXO experiment which will further reduce backgrounds by detecting the residual Ba ion produced in the decay. Installation of the EXO-200 detector is now in progress at the Waste Isolation Pilot Plant (WIPP) in New Mexico.
Keywords: Quantum Fields and Strings; Particle Physics; Cosmology